Penyelesaian Sengketa pada Perjanjian Tidak Tertulis dalam Hubungan Kerjasama Dagang Ditinjau dari Perspektif Hukum Perdata - Shera Tri Ambarini; Arief Rachman Hakim (CV Rewang Rencang, 2025)
Trade cooperation is a part of contract law within the scope of Indonesian civil law, which often involves both written and unwritten agreements. Business disputes in trade cooperation arising from unwritten agreements are unavoidable risks that can be resolved through arbitration or court proceedings. This study aims to examine the resolution of disputes in unwritten agreements from the perspective of Indonesian civil law. The findings indicate that all types of agreements, whether written or oral, are considered valid as long as they meet the requirements stipulated in Article 1320 of the Indonesian Civil Code. Furthermore, dispute resolution in trade cooperation relationships can be conducted through litigation or non-litigation mechanisms, including arbitration.